Retinoids activate the irritant receptor TRPV1 and produce sensory hypersensitivity - Yin, Shijin (American Society for Clinical Investigation, 2013)
Retinoids are structurally related derivatives of vitamin A and are required for normal vision as well as cell proliferation and differentiation. Clinically, retinoids are effective in treating many skin disorders and cancers. Application of retinoids evokes substantial irritating side effects, including pain and inflammation; however, the precise mechanisms accounting for the sensory hypersensitivity are not understood. Here we show that both naturally occurring and synthetic retinoids activate recombinant or native transient receptor potential channel vanilloid subtype 1 (TRPV1), an irritant receptor for capsaicin, the pungent ingredient of chili peppers. In vivo, retinoids produced pain-related behaviors that were either eliminated or significantly reduced by genetic or pharmacological inhibition of TRPV1 function. These findings identify TRPV1 as an ionotropic receptor for retinoids and provide cellular and molecular insights into retinoid-evoked hypersensitivity. These findings also suggest that selective TRPV1 antagonists are potential therapeutic drugs for treating retinoid-induced sensory hypersensitivity.